Novel Fluorescent Benzimidazole-Hydrazone-Loaded Micellar Carriers for Controlled Release: Impact on Cell Toxicity, Nuclear and Microtubule Alterations in Breast Cancer Cells - Rayna Bryaskova; Nikolai Georgiev; Nikoleta Philipova; Ventsislav Bakov; Kameliya Anichina; Maria Argirova; Sonia Apostolova; Irina Georgieva; Rumiana Tzoneva (MDPI AG, 2023)
Fluorescent micellar carriers with controlled release of a novel anticancer drug were developed to enable intracellular imaging and cancer treatment simultaneously. The nanosized fluorescent micellar systems were embedded with a novel anticancer drug via the self-assembling behavior of well-defined block copolymers based on amphiphilic poly(acrylic acid)-block-poly(n-butyl acrylate) (PAA-b-PnBA) copolymer obtained by Atom Transfer Radical Polymerization (ATRP) and hydrophobic anticancer benzimidazole-hydrazone drug (BzH). Through this method, well-defined nanosized fluorescent micelles were obtained consisting of a hydrophilic PAA shell and a hydrophobic PnBA core embedded with the BzH drug due to the hydrophobic interactions, thus reaching very high encapsulation efficiency. The size, morphology, and fluorescent properties of blank and drug-loaded micelles were investigated using dynamic light scattering (DLS), transmission electron microscopy (TEM), and fluorescent spectroscopy, respectively. Additionally, after 72 h of incubation, drug-loaded micelles released 3.25 μM of BzH, which was spectrophotometrically determined. The BzH drug-loaded micelles were found to exhibit enhanced antiproliferative and cytotoxic effects on MDA-MB-231 cells, with long-lasting effects on microtubule organization, with apoptotic alterations and preferential localization in the perinuclear space of cancer cells. In contrast, the antitumor effect of BzH alone or incorporated in micelles on non-cancerous cells MCF-10A was relatively weak.